2006
DOI: 10.2140/pjm.2006.228.277
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the contact Ozsváth–Szabó invariants

Abstract: In this paper we prove various results on contact structures obtained by contact surgery on a single Legendrian knot in the standard contact three-sphere. Our main tool are the contact Ozsváth-Szabó invariants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Thus Theorem 1 implies the following result. )) is independent of k and l. We are unable to say anything about the contactomorphism type of S 3 − (K n (k, l)), but in [15] it is shown that the Heegaard-Floer invariants of the S …”
Section: Examples Corollaries and Further Discussionmentioning
confidence: 84%
“…Thus Theorem 1 implies the following result. )) is independent of k and l. We are unable to say anything about the contactomorphism type of S 3 − (K n (k, l)), but in [15] it is shown that the Heegaard-Floer invariants of the S …”
Section: Examples Corollaries and Further Discussionmentioning
confidence: 84%
“…Consider a Legendrian knot L with a Thurston-Bennequin invariant tb(L) > 0 in (S 3 , ξ std ). Let (M, ξ) denote the contact 3-manifold results from a +1-contact surgery along a positive stabilization S + (L) of the Legendrian knot L. (M, ξ) is overtwisted by [24] and also c.f by [21]. Since tb(S + (L)) ≥ 0 according to the previous Remark 5.4, sg(S + (L)) > 0.…”
Section: Final Remarks and Questionsmentioning
confidence: 97%
“…We start with an open book adapted In this section we want to derive some applications of the theory developed in Section 4, Section 5 and Section 6. First to mention would be Proposition 7.1, which can also be derived using methods developed in [17]. There, Lisca and Stipsicz show that .C1/-contact surgery along stabilized Legendrian knots yield overtwisted contact manifolds, which implies the vanishing of the contact element.…”
Section: Implications To Contact Geometrymentioning
confidence: 97%